PENINGKATAN DAYA SAING USAHA MIKRO, KECIL, DAN MENENGAH “NASI BEBEK ALBISRI” DALAM BIDANG KULINER MELALUI PROSES PENDAFTARAN MEREK DAGANG - Putri, Kayla Fellicia; Joe, Cleo Patricia; Nareswari, Naura; Lestari, Hera Aprillya Dwi; Saputra, Rafi Rangga; Avesina, Darari Rifqi; Primandana, Devan Fakhriy; Ardiansyah, Aldizar Fikri; Andika, Alif; Haditama, Akbar; Rahayu, Monica Hermala; Dirkareshza, Rianda (Zhata Institut, 2026)
Intellectual Property Rights, particularly trademarks, play a vital role in strengthening business identity and competitiveness within the increasingly competitive culinary sector. However, many MSMEs have limited knowledge of the urgency of trademark protection and its registration procedures, making them vulnerable to business imitation risks. This community engagement program was conducted to support the culinary MSME “Nasi Bebek Albisri” in understanding the strategic benefits of trademark registration while providing direct assistance throughout the application process. The method used included counseling sessions consisting of material presentation, interactive discussions, and hands-on guidance during the preparation and submission of trademark documents to the Directorate General of Intellectual Property (DJKI). The results indicate a significant improvement in the MSME’s understanding of trademark functions, legal protection benefits, and administrative procedures involved in registration. Furthermore, the program successfully accompanied the MSME in completing its official trademark filing, thereby enhancing its business competitiveness and ensuring legal protection for its brand identity.